Automated manipulation of spherical objects in three dimensions using a gimbaled air jet - Becker, A.; Sandheinrich, R.; Bretl, T. (2009 IEEE/RSJ International Conference on Intelligent Robots and Systems, 2009)
This paper presents a mechanism and a control strategy that enables automated non-contact manipulation of spherical objects in three dimensions using air flow, and demonstrates several tasks that can be performed with such a system. The mechanism is a 2-DOF gimbaled air jet with a variable flow rate. The control strategy is feedback linearization based on a classical fluid dynamics model with state estimates from stereo vision data. The tasks include palletizing, sorting, and ballistics. All results are verified with hardware experiments.